Functional study of FleQ reveals the co-regulation of flgG by rpoN2vemRfleQ operon members in Xanthomonas citri subsp. citri - Gang Wang; Lanjuan Mi; Li Luo; Gaokai Li; Huasong Zou (iScience)
Summary: The transcription activator FleQ is responsible for the biosynthesis of flagella and other mechanisms in several bacteria. This study reported its regulatory role on EPS production, swimming, and virulence in Xanthomonas citri subsp. citri. Knockout and over-expression experiments revealed that the response regulator FleQ positively impacted virulence and cell motility, whereas it had a negative role in EPS production. FleQ interacts directly with the flgG promoter and participates in the positive regulation of the expression of flgG. Like RpoN2, FleQ physically interacted with VemR. In a complementation analysis of an rpoN2vemRfleQ operon deletion mutant, the restoration of swimming motility and activation of flgG required the presence of the entire rpoN2vemRfleQ operon. Together, our data suggest that FleQ plays multiple regulatory roles, especially activating the expression of flgG jointly with RopN2 and VemR in X. citri subsp. citri.